Outcomes of Uterine Artery Ligation Versus Internal Iliac Artery Ligation in Controlling Intractable Postpartum Hemorrhage - Sohaila Ameen, Rabia Razaq, Zareena Begum, Shahzada Amir Ahmed Babar, Aakif Yousaf, Mahpara Shaukat (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postpartum hemorrhage (PPH) remains a leading cause of maternal morbidity and mortality worldwide, particularly in low-resource settings. Objective: To compare the outcomes of uterine artery ligation and internal iliac artery ligation in controlling intractable postpartum hemorrhage for surgical effectiveness, operative parameters, and complication rates. Methodology: This was a retrospective comparative study conducted at Department of Obstetrics and Gynaecology, Saidu Group of Teaching Hospitals, Swat, and Sahiwal Teaching Hospital, Sahiwal from December 2022 to May 2023. A total of 109 patients diagnosed with intractable postpartum hemorrhage unresponsive to medical management were included in the study. Patients were retrospectively categorized into two groups based on the surgical intervention performed. Results: UAL had a significantly shorter operative time (55 ± 12 vs. 80 ± 15 minutes; p < 0.001) and lower blood loss (950 ± 220 vs. 1200 ± 270 mL; p = 0.001). Hemorrhage was successfully controlled in 90.6% of UAL cases and 95.5% of IIAL cases (p = 0.31). Emergency hysterectomy was required in 6.3% of UAL and 4.4% of IIAL patients (p = 0.69). The rate of postoperative complications was higher in the IIAL group (20.0% vs. 12.5%), though not statistically significant. The average hospital stay was significantly shorter in the UAL group (4.2 ± 1.1 vs. 5.6 ± 1.3 days; p = 0.003). Conclusion: Both uterine artery ligation and internal iliac artery ligation are effective in controlling intractable postpartum hemorrhage. UAL is associated with shorter operative time, reduced blood loss, fewer complications, and shorter hospital stay, making it a preferred first-line surgical option. IIAL remains valuable for refractory cases or when broader pelvic vascular control is needed. Keywords: Postpartum hemorrhage, uterine artery ligation, internal iliac artery ligation, obstetric emergency, maternal morbidity.